Morphological and genetic diversity of Beta maritima populations across Europe and North Africa: a comprehensive review - Bertram, Lisa; Frisch, Matthias (Frontiers in Plant Science, 2026)
Beta vulgaris ssp. maritima (sea beet), the wild ancestor of cultivated beet, represents a key reservoir of adaptive genetic diversity for sugar beet breeding. This review synthesizes research on morphological and genetic variation of Beta maritima populations across Europe and North Africa to (1) summarize regional diversity patterns, (2) assess the correspondence between phenotypic traits and genetic structure, and (3) identify knowledge gaps. Morphological studies show wide variation in sea beet. Growth habits range from prostrate to erect. Coastal plants often have thicker leaves and prostrate forms while inland types are adapted for water efficiency. Traits like pigmentation, inflorescence, and root shape also differ, reflecting adaptation to local environments. Bolting and flowering occur early in Mediterranean populations but are delayed in northern regions. Genetic analyses further identify a distinct Atlantic/Mediterranean divide. Mediterranean populations exhibit greater genetic diversity, while Baltic populations show low diversity and high homogeneity, presumably due to recent establishment and founder effects. Comparative findings suggest phenotypic variation often exceeds genetic differentiation and is strongly influenced by environmental factors. This review identifies research gaps among sea beet populations in Mediterranean regions particularly along the southern and eastern coasts of Spain, Italy, Greece, Turkey, and the eastern Mediterranean. As the first comprehensive review focused solely on Beta maritima in-situ populations, this work delivers a full account of the regions, traits, and genetic patterns studied to date. It establishes a foundation for future research and is an indispensable resource for advancing breeding, conservation, and scientific understanding of this important wild relative.